THE CORRELATION BETWEEN STUDENTS’ SELF ESTEEM AND STUDENTS’ SPEAKING ACHIEVEMENT AT UNIVERSITY OF ISLAM MALANG - TOMY MY PN (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2020)
Abstract: The aim of this research to find and describe the correlation between students’ self-esteem and their speaking achievement at University of Islam Malang. The method used was quantitative method with the correlational study as the research design of study. The population of this study was two semester students who enrolled in English Department of Faculty of Teacher Training and Education at University of Islam Malang, and 51 students were chosen using simple-random sampling technique. The researcher used questionnaire to obtain the students’ self-esteem and the researcher got the mid-term score of students’ speaking achievement from the lecturer. Then, the researcher calculated the students’ mid-term scores and the result of questionnaire using Pearson Product Moment Correlation to analyze the data. The result of correlation showed that r-observed of students’ self-esteem and speaking achievement was .183 with P value at .199. It can be inferred that P value was more than 0.05 or 0.199>0.05. The result indicated that the students’ self-esteem had no correlation with their speaking achievement. Also, it was found that self-esteem did not give impact for speaking ability and speaking achievement. So, it can be suggested that the students should focus on the speaking aspects not psychological aspect like self-esteem. Having been known the findings, the research highly suggested to English teachers and further researchers. First it is highly suggested to the English teachers to focus on the speaking technique than psychological aspect of the students. Furthermore, this study can give more understanding that psychological aspect is not really important in the way of learning speaking. Second, this study is also addressed to further researchers. The researcher recommends furthering research about some psychological aspects in the way of learning English skill other than speaking. Key words: Students’ self-esteem, speaking achievement, correlation